Tales told to Kabbarli - Wilson, Barbara Ker, 1929-; Bates, Daisy, 1861-1951; Thomas, Harold (New York : Crown Publishers, 1972)
A selection of Aboriginal legends of the Dreamtime collected by a white woman who lived among the Aborigines for more than forty years.
Keywords: Legends -- Australia -- Juvenile literature